GESTÃO ANALÍTICO-COMPORTAMENTAL DO DESEMPENHO - SILVA, Lucimara Leite (2021)
Performance is the individual’s behavior during the execution of an assignment. Behavior involves the relationship between antecedent events, response, and its consequences. In turn, performance management is about the identification of the control variables of behavior and their change for the fulfillment of personal and organizational goals. Furthermore, it is also considered a technology that seeks to improve people’s performance in the work environment, adding value to the organization and such practices structure themselves from the Behavior Analysis. Thus, the research objectives were to analyse the contribution from Behavior Analysis to performance management in organizations; verify how functional evaluation can be applied to performance management and identify the main techniques and procedures utilized in the behavior-analytic interventions in organizations. A narrative bibliographic search was conducted, in which articles, books, dissertations and theses were searched in the Scielo, Portal Periódico CAPES and Google Academic databases, with the descriptors in Portuguese: gestão de desempenho, avaliação do desempenho, desempenho and Análise do Comportamento and in English: performance management, performance appraisal, performance and behavior analysis. It was identified that the diagnosis of organizational problems made through functional assessment is widely utilised for the identification of the target behaviors, and evaluation of antecedent and consequential stimuli to the worker's behavior. Interventions focus on changes in such antecedents and consequents. The main identified techniques were setting goals and creating measurement systems for results, detailing of instructions, task clarification, feedback, changes in reinforcement schemes and reinforcement plan. In addition to being low-cost interventions, they are easily measurable and replicable, which allows for their reliability. The limitations of the research were due to the lack of material in the national literature, so it is suggested to expand the research.